Iz istorii ucastija gimnastov nasei strany v krupneiscich sorevnovanijach - Grigorev, A. E. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The author shows the parallel process of Russian gymnastic's development and its achievements in the international sports area. He analyses the reasons of victories and failures of the representatives of the domestic gymnastic school in the international level and gives the names of the outstanding russian gymnasts - champions and prize-winners of the Olympic Games and World Championships.